A New Composite Eyeball-Periorbital Transplantation Model in Humans: An Anatomical Study in Preparation for Eyeball Transplantation. Issue 4 (April 2018) - Siemionow, Maria; Bozkurt, Mehmet; Zor, Fatih; Kulahci, Yalcin; Uygur, Safak; Ozturk, Can; Djohan, Risal; Papay, Frank
Abstract : Background: Vascularized composite allotransplantation offers a new hope for restoration of orbital content and perhaps vision. The aim of this study was to introduce a new composite eyeball-periorbital transplantation model in fresh cadavers in preparation for composite eyeball allotransplantation in humans. Methods: The composite eyeball-periorbital transplantation flap borders included the inferior border, outlined by the infraorbital rim; the medial border, created by the nasal dorsum; the lateral border, created by the lateral orbital rim; and the superior border, created by the superior part of the eyebrow. The pedicle of the flap included the facial artery, superficial temporal artery, and external jugular vein. The skin and subcutaneous tissues of the periorbital region were dissected and the bony tissue was reached. A coronal incision was performed and the frontal lobe of the brain was reached by means of frontal osteotomy. Ophthalmic and oculomotor nerves were also included in the flap. After a "box osteotomy" around the orbit, the dissection was completed. Methylene blue and indocyanine green injection (SPY Elite System) was performed to show the integrity of the vascular territories after facial flap harvest. Results: Adequate venous return was observed within the flap after methylene blue dye injection. Laser-assisted indocyanine green angiography identified a well-defined vascular network within the entire composite eyeball-periorbital transplantation flap. Conclusions: For the first time, a novel composite eyeball-periorbital transplantation model in human cadavers was introduced. Good perfusion of the flap confirmed the feasibility of composite eyeball-periorbital transplantation in the clinical setting. Although harvesting of the flap is challenging, it introduces a new option for reconstruction of the periorbital region including the eyeball.